Effectiveness of organic adjuvant for control of tapping panel disease (TPD) of rubber trees (Hevea brasiliensis) / Ikhwani Fariha Ahmad - Ahmad, Ikhwani Fariha (Faculty of Plantation and Agrotechnology, 2015)
This research has been carried out in the plantation owned by Rubber research Institute Malaysia (RRIM) located in Kota Tinggi, Johor. Objective on these studies to observe whether microbial-based formulation and fertilizer derived from organic material can help by direct application to the tapping panel .of the rubber trees that have been infected by tapping panel disease (TPD) can revive back the phloem vessels and stimulate the production of the latex. This research has been done by using two types of Effective Microorganism (EM) base organic formulation that is Agroplus and BQ-65. The second objectives of this research is to observe changes in the phloem vessels and other tissues contained in the stem of the rubber tree that has been infected by the TPD by using electron microscope. The research has been done continuously for nine (9) weeks starting from 18th August until 22nd October 2014. Weekly data of the quantity of latex produced by the infected trees that have undergoes the treatment were recorded. The result shows that the microbe formulation (Agroplus) can help in stimulating the production of the latex. However, the degree of changes for the phloem vessels and other tissues contained in the stem of the rubber trees cannot be observed and analysed due to several factors.